Managing Risk and Performance : A Guide for Government Decision Makers - Stanton, Thomas H, 1944- (Wiley Finance Series)
Discover analytical tools and practices to help improve the quality of risk management in government organizations Federal agencies increasingly recognize the importance of active risk management to help ensure that they can carry out their missions.